Insect pheromones : the synthesis of the sex pheromone of Cryptoplebia leucotreta Meyr. and related compounds - Henderson, Howard Edward (Department of Chemistry, 2016)
The concept of pheromones is briefly expounded leading on to a discussion of the identified sex pheromones in the order Lepidoptera. The relationship between the structures Of these compounds and their biological activity is reviewed. A brief introduction to the sexual biology of tbe false codling moth (Gryptophlebia Leucotreta Meyr.) is given.